Transplant Hepatectomy With Portacaval Shunt and MARS Therapy for Perioperative Catastrophe: A Series of Four Liver Transplant Cases. Issue 3 (18th February 2021) - Cimeno, Arielle; Sultan, Samuel; Alvarez-Casas, Josue; Hanish, Steven I.; Bruno, David A.; Hutson, William R.; Stein, Deborah M.; Scalea, Thomas M.; Barth, Rolf N.; LaMattina, John C.
Abstract : Background: Increased worldwide focus on maximal donor utilization and transplantation of patients once considered too ill to survive liver transplantation may increase the otherwise rare frequency of catastrophic graft failure. Although the deleterious effects of an acutely failing allograft have been established for decades, the optimal strategy in this patient population in the perioperative period remains ill-defined. Methods: A retrospective review of all liver transplant recipients with perioperative failure leading to transplant hepatectomy between January 1, 2014 and June 30, 2017 was performed. All patients were supported with MARS therapy while awaiting retransplantation. Results: Four patients experienced catastrophic graft failure from massive exsanguination and liver fracture (1), portal vein and hepatic artery thrombosis (1), idiopathic necrosis (1), and necrosis from inadequate donor flushing/primary nonfunction (1). All patients improved following transplant hepatectomy with portacaval shunting. Patients were supported with intubation, vasopressors, renal replacement therapy, and Molecular Adsorbent Recirculating System therapy. All patients underwent retransplantation after a mean anhepatic phase of 48.8 (± 5.13) h. Survival to discharge was 75%. Conclusions: Although catastrophic liver failure is highly challenging, acceptable outcomes can be achieved with timely hepatectomy with portacaval shunt and retransplantation, particularly in patients supported with the Molecular Adsorbent Recirculating System device.